The values of m and p are m = 9 , p = -7
Step-by-step explanation:
To simplify the polynomials:
∵ (my²- 4y + 3) - (5y² - 2y - p)
- Multiply each term of the second bracket by (-) to open it
∴ my² - 4y + 3 - 5y² + 2y + p
- Collect the like terms
∴ (my² - 5y²) + (-4y + 2y) + (3 + p)
- Add them
∴ (m - 5)y² + (-2) y + (3 + p)
∴ (m - 5)y² - 2y + (3 + p)
∵ The simplified form of the expression is 4y² - 2y - 4
∴ (m - 5)y² - 2y + (3 + p) = 4y² - 2y - 4
- Compare the like terms and equate them
∵ (m - 5)y² = 4y²
∴ m - 5 = 4
- Add 5 to both sides
∴ m = 9
∵ 3 + p = -4
- Subtract 3 from both sides
∴ p = -7
The values of m and p are m = 9 , p = -7
Learn more:
You can learn more about polynomials in brainly.com/question/9500387
#LearnwithBrainly